The Body Mass Index Profile of PE Teachers in Semarang City during the Covid-19 Pandemic - Rahayu, Setya; Soegiyanto, Soegiyanto; Setiawan, Ipang; Faza, Ricka Ulfatul (Journal of Physical Education Health and Sport, 2020)
The Covid-19 pandemic requires teachers and students to carry out online learning. This has an impact on physical education subject. It definitely reduces the physical activity in which physical education, sports and healthÂ  requires physical activity as a medium of learning. The lack of physical activity has a negative effect on health and physical fitness. This study aims to analyze the physical fitness of Physical Education Teachers (PE Teachers) in Semarang City during the Covid-19 pandemic based on the Body Mass Index (BMI). The research method used was a survey, the research sample was 186 PE Teachers in Semarang. The data collection was gained by the measurements of height and weight. BMI is calculated using the formula of the body mass divided by the square of the body height in units of kg/m2. The quantitative data analysis used in this study was the percentage to describe the physical fitness profile based on BMI. The results of the study showed that the BMI of Semarang City PE Teachers during the Covid-19 pandemic were as follows: underweight 7 people (3.76%); normal or healthy weight 115 people (61.83%), overwight 56 people (30.11%), obese 8 people (4.30%). The conclusion of the physical fitness of PE Teachers in Semarang City during the Covid-19 pandemic based on body mass index were catagorized as folows: the underweight were 7 people (3.76%), normal or healthy weight were 115 people (61%), overweight and obese were 64 people (34.41%). The suggestions for PE Teachers whose category are underweight, overweight and obese based on BMI is to evaluate and improve their lifestyle, diet and physical activity so that their body weight becomes normal or ideal and their physical fitness is getting better. For those who acquired normal category, it means they have been having a good lifestyle.